Pengaruh Literacy Food Terhadap Kualitas Hidup Perempuan Penambang Emas Skala Kecil Di Desa Logas Kabupaten Kuantan Singingi - Toti Indrawati; Hilmah Zuryani; Rahmita Budiartiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of food literacy on the quality of life of women small-scale gold miners in Logas Village, Kauntan Singingi Regency. Data was collected through literature and documentation studies as well as field surveys with the respondents being: women small-scale gold miners in Logas Village, Kuantan Singingi. The analysis uses qualitative descriptive. The results of the research show that the Food Literacy Component of ASGM Women in Logas village is categorized as good so that the knowledge of ASGM women in Logas village is good. The income ASGM women in Logas village exceeds the poverty line and 1 is borne by the husband. Even though their knowledge of food literacy is good, it is not intentional because of their low level of education so they cannot read, the income of ASGM women in Logas village can meet their food needs, food literacy affects the quality of life of ASGM women in Logas village.